Mainstreams of Research on Institutional Change in the Multidimensional Viewpoint - Marek Piosik (Institute of Economic Research (IER), 2017)
The role of institutions in the social and economic development is widely recognized in recent literature on economics of institutions. Economic history provides many examples of bad and good institutional structures, environments, and ways of organizing the social life and relationships between individuals, which is the main reason for institutions to arise. Simultaneously diversity of institutional solutions can be perceived as cultural wealth from which societies can choose in order to find proper instruments to solve various problems in different situations. The present paper is an attempt to review main areas of research into institutional changes and synthesize them into mainstreams, which are also described in the multi-faceted viewpoint to prove the complexity and broad scope that need to be tackled by institutional economists to investigate institutional changes. The article analyses literature on institutional change and several dozen dimensions of the research areas that have a significant impact on the discussion on the mechanisms and environments of evolution of institutions. The review of the mainstreams is divided into five identified basic groups. In the last section the multidimensional perspective of the research area of institutional changes is proposed as it helps to grasp many aspects that play the fundamental role in understanding the process of institutional change, which is an indispensable step towards a development of the general theory of institutional change.
Keywords: B52; D02; O17; O43; 330; institutions; institutional change; theory of institutional change; evolution of the institution